Optical Chemical Sensing of Iodide Ions: A Comprehensive Review for the Synthetic Strategies of Iodide Sensing Probes, Challenges, and Future Aspects. Issue 7 (17th May 2022) - Mansha, Muhammad; Akram Khan, Safyan; Aziz, Md. Abdul; Zeeshan Khan, Abdul; Ali, Shahid; Khan, Majad
Abstract: Among several anions, iodide (I − ) ions play a crucial role in human biological activities. In it's molecular form (I2 ), iodine is utilized for several industrial applications such as syntheses of medicines, fabric dyes, food additives, solar cell electrolytes, catalysts, and agrochemicals. The excess or deficiency of I − ions in the human body and environmental samples have certain consequences. Therefore, the selective and sensitive detection of I − ions in the human body and environment is vital for monitoring their overall profile. Amongst various analytical techniques for the estimation of I − ions, optical–chemical sensing possesses the merits of high sensitivity, selectivity, and utilizing the least amount of sensing materials. The distinctive aims of this manuscript are (i) To comprehensively review the development of optical chemical sensors (fluorescent & colorimetric) reported between 2001–2021 using organic fluorescent molecules, supramolecular materials, conjugated polymers, and metal‐organic frameworks (MOFs). (ii) To illustrate the design and synthetic strategies to create specific binding and high affinity of I − ions which could help minimize negative consequences associated with its large size and high polarizability. (iii) The challenges associated with sensitivity and selectivity of I − ions in aqueous and real samples. The probable future aspects concerning the optical chemical detection of I − ions have also been discussed in detail. Abstract : The distinctive aim of this manuscript is to comprehensively review the development of optical chemical sensors for iodide ions sensing, their design and synthetic strategies to avoid limitations concerning its large size and high polarizability, and challenges in real samples as well as probable future aspects.